Macro-Regional Analysis of Tourism Entrepreneurship Environment in Bali: A Descriptive Study - Donny Susilo (International Journal of Economics, Business, and Entrepreneurship, 2020)
Bali has always become a world-class famous tourism destination since a long time ago. Entrepreneurship development in Bali is needed because it can create job for local people and maximize the utilization of local resource for regional growth and development. This research aims to understand tourism entrepreneurship environment in Bali based on macro-regional analysis. This research used PESTEL framework and secondary data from various sources to analyze external environment of Bali as a place to develop tourism entrepreneurship. This research also conducted seasonal analysis from secondary data to understand characteristic of tourism market in Bali. The research founded that governments actively promoted Bali as world-class tourism destination, while at the same time provided grant for green project. Through their investment coordinating board, governments also helped investor to enter Indonesia market easily and conveniently. In economic aspect, tourism industry growth is seasonal but prospective because the economic growth in Bali is visibly good and stable. While setting up business in Bali needs basic knowledge in local Hindu culture, the technology infrastructure in Bali still needs improvement especially related to internet speed. Green project is important because Bali has significant environmental issue on recently, which also becomes opportunity for entrepreneurs to innovate. The protection law and legal standing for entrepreneurs in Bali is basically available but still need improvement, especially in the field of start-up taxation, garbage reduction and green project regulation.